2014
DOI: 10.1111/jomf.12115
|View full text |Cite
|
Sign up to set email alerts
|

Generous or Greedy Marriage? A Longitudinal Study of Volunteering and Charitable Giving

Abstract: Recent scholarship has explored whether marriage encourages individuals to contribute to or withdraw from society. The authors examined how marriage affects volunteering and charitable giving, using longitudinal data from the 2001 to 2009 waves of the Panel Study of Income Dynamics. Newly married men, but not women, were significantly more likely to give money to charity in the first survey wave after marriage and gave larger amounts of money. Newly married women, but not men, were significantly less likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 43 publications
2
27
1
Order By: Relevance
“…There have been several general studies of volunteerism published since the onset of the Great Recession [18][19][20][21][22][23][24][25][26][27][28][29][30]. This research found a wide range of factors other than race correlated with volunteerism.…”
Section: Researchmentioning
confidence: 78%
“…There have been several general studies of volunteerism published since the onset of the Great Recession [18][19][20][21][22][23][24][25][26][27][28][29][30]. This research found a wide range of factors other than race correlated with volunteerism.…”
Section: Researchmentioning
confidence: 78%
“… 50,0 1998 12 7 Volunteering {Yes vs. No} Voluntary work carried out in the past 12 months Formal 2914 w 40,0 u / 41,5 v N.R. Einolf & Philbrick [ 26 ] PSID x USA Individuals never married at baseline N.R. N.R.…”
Section: Resultsmentioning
confidence: 99%
“…2a ). Six studies [ 11 , 21 , 24 , 26 , 30 , 36 ] (out of eleven) found that older people are less likely to volunteer, no associations in the opposite direction were found. Sources of heterogeneity were explored by conducting meta-regression analyses and subgroup analyses (see Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, they found that the effects of religion on both the decision to give financially and the amount given were moderated by religious affiliation, with religion having the biggest effect for Christians. Other predictors of financial giving include peer support (Prendergast & Maggie, 2013), being married (Einolf & Philbrick, 2014), and similarity and connection between giver and receiver (Prendergast & Maggie, 2013). Although financial ability has been found to predict financial giving (Prendergast & Maggie, 2013), research has not yet established if and how SES might be associated with financial giving.…”
Section: Financial Givingmentioning
confidence: 99%